2010
DOI: 10.3762/bjoc.6.74
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking and structure of a mixture of nematic liquid crystals and anisotropic nanoparticles

Abstract: SummaryOrientational ordering of a homogeneous mixture of uniaxial liquid crystalline (LC) molecules and magnetic nanoparticles (NPs) is studied using the Lebwohl–Lasher lattice model. We consider cases where NPs tend to be oriented perpendicularly to LC molecules due to elastic forces. We study domain-type configurations of ensembles, which are quenched from the isotropic phase. We show that for large enough concentrations of NPs the long range uniaxial nematic ordering is replaced by short range order exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We explained this as follows: If the underlying FLC material is composed of any free radical (unpaired electron), the interaction among the FM NPs exchange field (due to unpaired e À ) and FLC molecular director would be much greater than the kind of interaction previously predicted for diamagnetic FLCs in Ref. 24. The FLC mixture used for present study consists of two basic compounds:…”
Section: -3mentioning
confidence: 92%
See 1 more Smart Citation
“…We explained this as follows: If the underlying FLC material is composed of any free radical (unpaired electron), the interaction among the FM NPs exchange field (due to unpaired e À ) and FLC molecular director would be much greater than the kind of interaction previously predicted for diamagnetic FLCs in Ref. 24. The FLC mixture used for present study consists of two basic compounds:…”
Section: -3mentioning
confidence: 92%
“…This fact was later proved experimentally by Chen and Amer 21 in their investigation on "ferronematics" and motivated many successive studies thereon. [22][23][24] Now, It is not only limited to the FM characteristic of NPs but the size and morphology of NPs have also been found to beautifully engage themselves in tuning the properties of nematic and ferroelectric LC mixtures. 23 For example, Nematic LCs and the chiral nematic LCs could be perfectly aligned in homeotropic and planar geometries by doping a trace of Ni nanospheres and nanobowels owing to the morphology and surface adsorption of FM NPs on underlying substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that the electric field associated with NPs can influence the local orientational ordering, increase the isotropicnematic (I-N) transition temperature or decrease the switching voltage [1,2,[10][11][12]. All these have led to an increase of theoretical and experimental interest in LC-based nanocolloids [17][18][19][20][21][22][23][24][25][26][27][28][29]. Regarding experiments, particularly important are dielectric studies since they are strongly associated with practical implementations and their results can be compared with fundamental models of the physics of liquid crystal .…”
Section: Introductionmentioning
confidence: 99%
“…We henceforth refer to − → n i ( − → m i ) as the nematic (magnetic) spin. The interaction energy E of the system is given by (Cvetko et al, 2009;Krasna et al, 2010;Lebwohl & Lasher, 1972)…”
Section: Interaction Energymentioning
confidence: 99%